Measurement of Gallbladder Volume with Ultrasonography in Pregnant Women. (1st May 2000) - Kapicioglu, Sait; Gürbüz, Sevgi; Danalioglu, Ahmet; Sentürk, Ömer; Uslu, Mehmet
Abstract : Fasting and postprandial gallbladder volumes were investigated using ultrasonography in three groups (10 subjects in each) of healthy women: third trimester pregnant women, postpartum women up to 10 days after giving birth and nonpregnant controls. The scans were performed at 09:00 after a 12 h fast. After the basal measurement was taken, gallbladder volumes were rescanned in 15 min intervals for 60 mins. At the end of this period, all volunteers received a standard liquid test meal, and scans were performed again for 1 h. The mean basal gallbladder volume was 22.2±4.2 mL in the nonpregnant (control) group. In the third trimester group, the basal volume was 37.8±10.5 mL – 70.5% higher than in the nonpregnant group (P<0.001). In the postpartum group, the mean basal volume was 37.9% lower (27.4±6.5 mL) than that of the third trimester group (P<0.02). This basal volume was 23.6% greater than that of the control group (P<0.05). After administration of a test meal, the postprandial gallbladder volumes decreased during the first few minutes compared with baseline values. The volumes decreased by 10.2% to 39.8% (23.5±7.3 to 34.0±10.2; P<0.01) in the third trimester group, by 14.9% to 43.2% (16.6±4.3 to 23.3±5.5; P<0.01, 0.001) in the postpartum group and by 19.2% to 51.6% (11.9±3.5 to 17.9±3.6; P<0.02, 0.05, 0.01, 0.001) in the control group. Postprandial mean gallbladder volumes of the third trimester (P<0.02) and postpartum groups (P<0.02 to 0.01) were significantly different from those of the control group. In conclusion, incomplete emptying of the gallbladder after eating during the third trimester of pregnancy may contribute to cholesterol-gallstone formation, and pregnancy may thus increase the risk of gallstones.